Application of the method of ultrasound imaging in the removal of foreign bodies in gunshot wounds. - Svitlychnyi, E. V.; Muradian, K. R.; Herasymenko, O. S.; Koshykov, M. O.; Haida, Ya. I.; Yenin, R. V. (Medicni Perspektivi, 2018)
Data on the possibility of using ultrasound diagnostics when removing foreign bodies - bullets and fragments from body tissues during primary or repeated surgical treatment are rather limited. The aim of the research – improving the results of treatment of victims with gunshot fragmentation and bullet wounds by using a complex of ultrasound and X-ray navigation in the process of removing injurious elements during primary and repeated surgical treatment. The study included 214 wounded. In group I, the main group (122 wounded), the removal of fragments was carried out using a complex of X-ray and ultrasound navigation. In group II, the control group (92 wounded), only X-ray navigation was used. In group I during primary surgical treatment, foreign objects were removed in 101 (82.8%) of 122 injured and during secondary – in 17 (13.9%). In group 4 (3.3%) patients, the fragments were not visualized: in 1 - in the lateral region of the neck, in 1 - in the muscles of the leg, in 2 - in the chest wall. Complications were not observed. In group II, during primary surgical treatment, foreign objects were removed in 59 (64.1%), and in the secondary – in 18 (19.6%). The reasons for the failures were: deep lieying of fragments - in 6 (6.5%), location near large vessels - in 5 (5.4%), non-X-ray contrast foreign bodies - in 4 (4.3%). Among the complications, bleeding was observed in 2 wounded. The use of ultrasound navigation allows by 18.7% to increase the frequency of detection and removal of foreign bodies - bullets and fragments during the primary surgical treatment of a wound and to reduce the need for repeated interventions by 5.7%. The advantages of the method are: mobility, high information content in structural damages to soft tissues and verification of foreign bodies, the possibility of performing real-time, the absence of exposure to radiation.